(untitled) (Al-Qamar, 2021)
This article presents a study of “Ḥayāt-i-Sarwar-i-Kā’ināt”, an Urdu book on Sīrah of Prophet Muhammad (ﷺ), by Mullā Wāḥidī (1888-1976), a prominent author and journalist of Indo-Pak subcontinent and a disciple of renowned Indian Sufi saint Khwāja Ḥassan Nizāmī (1873-1955). The Study finds the book unique in terms of its style and content. The author has presented the themes in simple, literary and attractive way. Each and every event of the life of the Prophet is stated in the form of a comprehensive essay. Views of various writers have been reproduced to strengthen the arguments. All the related events have been described systematically.